(3dHGH GdbhJ ef NRGfI GdedchJs - (3eMehO Hf Ydj Hf eMeO GdcGTj GdfWfRj,J (B735 (3g` s ((3eMeO Hf CHj YHO Gddg eMeO Hf eMeO Hf YKeGf GdTjN s)
(3ChdgG (B:s
(3GdMeO ddg GdPi cTa Yf Xde GdEYOGe HdeYGf fhQ hLhOg EYde CjgG GdeJYWT Edi RdGd Gdjbjf Cf GdQHhHjg ai XghQgG Ydi eG jTgO dg GdYbd hGdfbd s
(3BNQgG (B:s
(3aai cd hbJ bWH gh Cced GdfGS ai Pdc GdhbJ hjMSH LejY GdChbGJ bWH gh Cced GdCbWGH hgh hLhO GdfHi Udi Gddg Ydjg hSde GdPi gh Cced GdChdjf hGdBNQjf addg GdMeO ChdkG hBNQkG hHGWfkG hXGgQkG Ydi Jhajb GdSOGO s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1542s
Keywords: (3GdJUha hGdBOGH GdTQYjIs